A 120-year sedimentary record and its environmental implications, in a dated marine sediment core from Daya Bay in the northeastern South China Sea. (August 2019) - Zhou, Peng; Li, Dongmei; Zhao, Li; Li, Haitao; Ni, Zhixin; Zhao, Feng; Yu, Hansheng; Li, Xiaomin
Abstract: In a Daya Bay 120-year dated sediment core(1892–2010), analyses were conducted of grain-size, water content, TOC, TIC, TC, loss on ignition, TN, BSi and TP, to reconstruct the anthropogenic activity history. The entire core was divided into four periods. Multi-parametric measurements, their ratios and interrelations are seen to clearly reflect the development of agriculture, aquaculture, industry and social economy surrounding Daya Bay. The trends of TOC, TOM and BSi after 1990 may be due to mass input of nutritious matter from aquaculture and industry, whereas the trends of BSi, TOC and TOM between 1960 and 1990 were owing to aquaculture and agriculture. Two peaks of BSi, TOC and TOM in 1994 and 2002 imply that the mass input of cooling water from nuclear power plants may be a significant contributor to ecological environment changes. Finally, some proposals were put forward for the healthy and sustainable development of Daya Bay. Highlights: Environment change and anthropogenic activity was reconstructed based on a 120 year-dated sediment core. Grain-size, water content, TOC, TIC, TC, LOI, TN, BSi and TP in the sediment core were analyzed. The core was divided into four periods according to the profiles of TOC, TIC, TC, LOI, TN, BSi, TP, grain-size, and so on. Multiple proxies, their ratios and interrelations are seen to clearly reflect the environment change surrounding Daya Bay. Daya Bay has been severely impacted due to the rapid economic development and population growth after 1980s.